Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Minat Berkunjung Ulang melalui Kepuasan Konsumen yang Menginap di Natuna Dive Resort, Kepulauan Riau - Fitriana Baitanu; Hetty Yulianti Sihite; Ida Rahayu; Andre Junianda (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to examine the influence of service quality and facilities on revisit intention through customer satisfaction at Natuna Dive Resort, Riau Islands. The research employed a quantitative approach, with data collected through questionnaires distributed to 155 respondents who were resort guests between January and December 2024. Instrument feasibility was assessed using validity and reliability tests, while data were analysed through multiple linear regression, including both partial and simultaneous significance tests. The findings reveal that both service quality and facilities significantly and positively affect guests’ revisit intention, with service quality emerging as the more dominant factor. The coefficient of determination (R²) of 0.602 indicates that 60.2% of the variance in revisit intention can be explained by the two independent variables, while the remaining percentage is influenced by external factors not covered in this model. This research highlights the crucial role of improving service quality and managing facilities sustainably to enhance guest loyalty in the hospitality sector—particularly in tourism destinations that offer natural and cultural uniqueness, such as Natuna Dive Resort. The results of this study may serve as a practical reference for resort managers in developing consumer experience-based marketing and service improvement strategies.